Labelling of membrane glycoproteins of cultivated Plasmodium falciparum - Udeinya, Iroka J. (1980)
Membrane glycoprotein synthesis by Plasmodium falciparum was determined by metabolic labelling in the presence of 74 kBq/ml (2.5 μCi/ml) glucosamine-(3)H. Five major glycoprotein bands and four minor ones were demonstrated. A control experiment using normal, outdated, human erythrocytes indicates that there was no incorporation of the labelled glucosamine into the erythrocyte membrane. It was also demonstrated that the rate of membrane glycoprotein synthesis by mature parasites of the trophozoite and schizont stages was twice that of the ring-stage parasites. Cytochemical surface-labelling experiments had led to the conclusion that the membrane of malaria parasites contains little or no glycoprotein. Our studies indicate, however, that there is significant synthesis of membrane glycoprotein by the parasite and that this can be metabolically labelled and measured by using radioactive glucosamine as precursor of the glycoprotein.